2016
DOI: 10.1126/science.aaf6793
|View full text |Cite
|
Sign up to set email alerts
|

Direct time-domain observation of attosecond final-state lifetimes in photoemission from solids

Abstract: Attosecond spectroscopic techniques have made it possible to measure differences in transport times for photoelectrons from localized core levels and delocalized valence bands in solids. We report the application of attosecond pulse trains to directly and unambiguously measure the difference in lifetimes between photoelectrons born into free electron-like states and those excited into unoccupied excited states in the band structure of nickel (111). An enormous increase in lifetime of 212 ± 30 attoseconds occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
182
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 211 publications
(193 citation statements)
references
References 68 publications
(8 reference statements)
10
182
1
Order By: Relevance
“…The associated time delay can be clearly seen in the experimentally measured interferograms of Cu(111) as an obvious phase shift in the oscillations of the RABBITT quantum interferences (Fig. 3B), which interestingly is absent in Ni(111) for free-electron final states (33). We note that we can exclude the possibility that the finite photoelectron lifetime in this energy range in Cu(111) is caused by another final-state resonance because we did not observe any photoelectron yield enhancement in this energy range (Fig.…”
Section: Methodsmentioning
confidence: 94%
See 3 more Smart Citations
“…The associated time delay can be clearly seen in the experimentally measured interferograms of Cu(111) as an obvious phase shift in the oscillations of the RABBITT quantum interferences (Fig. 3B), which interestingly is absent in Ni(111) for free-electron final states (33). We note that we can exclude the possibility that the finite photoelectron lifetime in this energy range in Cu(111) is caused by another final-state resonance because we did not observe any photoelectron yield enhancement in this energy range (Fig.…”
Section: Methodsmentioning
confidence: 94%
“…The photoelectron spectrum is then collected using a hemispherical photoelectron analyzer (Specs Phoibos 100). Note that it has already been shown that RABBITT and attosecond-streaking yield the same temporal information about the photoemission process (31), whereas ARPES adds significant advantages of band specificity (33). Moreover, by simultaneously measuring two photoelectron wavepackets from different initial states excited by the same harmonic orders we can eliminate the influence of the HHG phase (28).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the simplest semi-classical picture of HHG, the electron can return to the parent ion with high kinetic energy and then any excess energy greater than the ionization potential can then be emitted as a high-harmonic photon. When the HHG process is properly phase matched, a bright coherent beam of extreme ultraviolet (EUV) or soft X-ray light is generated [6][7][8][9][10], which can be used to uncover coupled dynamics in materials with femtosecond-to-attosecond temporal resolution [11][12][13][14][15], and can also be used for high-resolution imaging [16][17][18][19]. Alternatively, if the electron does not recombine upon re-encountering the ion it may rescatter from the ion, encoding information about the sub-ångström and sub-femtosecond structure of the scattering potential into the photoelectron momentum distribution [20][21][22].…”
Section: Introductionmentioning
confidence: 99%